Touch static analysis and dynamic exercises of insulated patients - Vakhitov, B.I.; Raginov, I.S.; Vakhitov, I. Kh.; T. L. Zefirov, T. L.; Khisamutdinov, R.E. (Revista de la Universidad del Zulia, 2019)
For the first time, studies were conducted on the study of the amplitude indices (C-EMG) and the frequency of the oscillations following (CSC-EMG) when performing dynamic and static exercises among patients with stroke and healthy people. It was revealed that in healthy individuals (control group) the amplitude of the EMG depends on the nature of the exercises. The largest EMG amplitude is registered when performing static exercises. It was found that patients who were hospitalized in the acute period of stroke when flexion and extension of the fingers were performed were mainly recorded low-amplitude movement stretched for the entire cycle without a clear peak of the extremum of EMG activity. When performing static exercises in these patients, a greater amplitude and an increase in the frequency of the EMG oscillations were revealed.